Non-specific phospholipase C4 mediates response to aluminum toxicity in Arabidopsis thaliana - Pejchar, Přemysl; Potocký, Martin; Krčková, Zuzana; Brouzdová, Jitka; Daněk, Michal; Martinec, Jan (Frontiers in Plant Science, 2015)
Aluminum ions (Al) have been recognized as a major toxic factor for crop production in acidic soils. The first indication of the Al toxicity in plants is the cessation of root growth, but the mechanism of root growth inhibition is largely unknown. Here we examined the impact of Al on the expression, activity, and function of the non-specific phospholipase C4 (NPC4), a plasma membrane-bound isoform of NPC, a member of the plant phospholipase family, in Arabidopsis thaliana. We observed a lower expression of NPC4 using β-glucuronidase assay and a decreased formation of labeled diacylglycerol, product of NPC activity, using fluorescently labeled phosphatidylcholine as a phospholipase substrate in Arabidopsis WT seedlings treated with AlCl3 for 2 h. The effect on in situ NPC activity persisted for longer Al treatment periods (8, 14 h). Interestingly, in seedlings overexpressing NPC4, the Al-mediated NPC-inhibiting effect was alleviated at 14 h. However, in vitro activity and localization of NPC4 were not affected by Al, thus excluding direct inhibition by Al ions or possible translocation of NPC4 as the mechanisms involved in NPC-inhibiting effect. Furthermore, the growth of tobacco pollen tubes rapidly arrested by Al was partially rescued by the overexpression of AtNPC4 while Arabidopsis npc4 knockout lines were found to be more sensitive to Al stress during long-term exposure of Al at low phosphate conditions. Our observations suggest that NPC4 plays a role in both early and long-term responses to Al stress.